Place-making and the bordering of urban space: Interpreting the emergence of new neighbourhoods in Berlin and Budapest. (July 2019) - Scott, James W; Sohn, Christophe
The objective of this paper is to theorize border-making processes in urban contexts as exemplary of the ways in which borders within human societies are formed. In fact, the question as to whether socially meaningful borders are created through state-society and systemic relations or whether they ultimately emerge locally out of social relations is not as trivial as it might seem. The concept of 'bordering' implies non-finalizable processes in which socio-spatial distinction is constantly created, confirmed and challenged. Far from being solely a product of state territoriality and international relations, borders are also social institutions that are constantly created, maintained and re-created as a means of negotiating the complexities of everyday life. Urban contexts reveal much about the rationales and mechanisms behind bordering processes. Our concrete bordering focus is related to place and to place-making processes that reflect the attributions, appropriations and representations of place ideas. As is argued in this paper, urban borders are a nexus between everyday practices of differentiating social space, the instrumentality of place-making, for example, as a project of urban development, and the ontological need for a sense of rootedness in place. Two case studies of urban change in Budapest and Berlin will be developed that illustrate this nexus.